Taurine Attenuates the Hypotaurine-Induced Progression of CRC via ERK/RSK Signaling - Hou, Xiaodan; Hu, Junwei; Zhao, Xinyu; Wei, Qing; Zhao, Rongping; Li, Min; Li, Qiong (Frontiers in Cell and Developmental Biology, 2021)
Colorectal cancer (CRC) is one of the most common malignant tumors, and previous metabolomics work has demonstrated great promise in identifying specific small molecules of tumor phenotype. In the present study, we analyzed the metabolites of resected tissues through gas chromatography-mass spectrometry (GC-MS), and found that the concentration of taurine in CRC tissues diminished whereas the concentration of hypotaurine increased. The results in vitro demonstrated that taurine significantly suppressed cellular proliferation, metastasis, and colony formation whereas it induced apoptosis in CRC cells. Furthermore, taurine regulated the expression levels of epithelial mesenchymal transition (EMT)-associated genes in a dose-dependent manner. Taurine also alleviated hypotaurine-induced CRC progression, which was linked to the inhibition of the ERK/RSK-signaling pathway and diminution in intracellular hypotaurine. Taurine additionally attenuated hypotaurine-induced tumor growth and metastasis in vivo. Patients with CRC exhibited lower levels of serum taurine, suggesting that taurine might be a promising biomarker reflecting a poor prognosis in CRC. Collectively, our results demonstrated that taurine-attenuated, hypotaurine-induced CRC progression provides a potential target for CRC therapy.